Corporate Governance and Financial Performance: The Family SMEs a Special Case (Global Journal of Human-Social Science, 2022)
This paper aims to present the results of a survey on the impact of internal governance, particularly ownership structure on financial performance. Using a multiple regression analysis on data collected from 190 Moroccan family-owned SMEs, we will study this relationship under different aspects, namely: the ownership of the manager, the concentration of capital and the nature of the shareholding. After conducting tests on the relationship between ownership structure variables and the financial performance of family SMEs, we were able to raise some results that underlie this research. The first is that managerial ownership has a positive effect on financial performance, which confirms the convergence of interests thesis supported by Jensen and Meckling. Similarly, we find the effective existence of a non-linear relationship between managerial ownership and financial performance. The second result is consistent with the neutrality thesis of Demsetz and Lehn who showed that ownership concentration has no effect on firm value. And as for the nature of the shareholding, a positive and nonsignificant association between the percentage of capital held by members outside the family and financial performance was clearly demonstrated.
Keywords: « family business »; « SME »; « ownership structure »; « financial performance »